Built for the people: crafting a demand-driven affordable housing model in Selangor - Ahmad Tajuddin, Hidayatul Najiha; Nasir, Zarul Azhar; Ahmad Kusairee, Muhammad Adidinizar Zia; Rahma, Ainol Mardhiyah (2025)
Despite numerous government initiatives, Selangor’s affordable housing sector continues to face persistent challenges such as oversupply, property overhang, and a high rate of rejected offers. This mismatch between supply and actual demand highlights a gap in existing definitions and criteria, which often fail to reflect the real needs of prospective homeowners. To address this, a new model for affordable housing in Selangor was developed, integrating foundational definitions and demand-driven criteria based on the perspectives of multiple stakeholders, including homebuyers, developers, and policymakers. The framework captures key elements such as financial aspects, property specifications, accessibility, safety, developer reputation, and government intervention, while aligning with regulatory requirements like price caps of RM300,000, household income limits, and first-home eligibility for Malaysian citizens. This model aims to bridge the gap between housing supply and public demand, providing a more comprehensive approach that addresses financial constraints and enhances the overall quality of life for residents. It offers valuable insights for policymakers, developers, and housing authorities in creating sustainable, demand-driven housing solutions that genuinely meet the needs of Selangor’s diverse population.